Suppression of Xanthomonas oryzae pv. oryzae infection in rice seeds: investigating the optimal temperature and packaging conditions for enhanced pathogen control and seed quality - Nikko; Evan Purnama Ramdan; Risnawati; Herik Sugeru (Jurnal Ilmiah Pertanian, 2023)
The pathogen Xanthomonas oryzae pv.oryzae (Xoo) is responsible for rice bacterial leaf blight (BLB), a disease that can significantly reduce rice yield by 60-80%. Xoo can also be transmitted through seeds, making it a seed-borne pathogen. Therefore, it is crucial for farmers to consider environmental factors when storing seeds. This research aims to determine the optimal temperature and packaging for storing rice seeds to prevent Xoo infection. The study employed a split-plot design, where the main plot consisted of two temperature treatments: low (4 ᵒC ± 2 ᵒC) and room temperature (28 ᵒC ± 3 ᵒC). The subplots focused on three packaging types: no packaging as a control, aluminum foil, and polyethylene plastic, resulting in a total of six treatment combinations. Seed pathology testing was conducted using the liquid assay method, while physiological testing utilized the growing on test method. The results revealed that plastic packaging at room temperature provided the most effective treatment for suppressing Xoo, exhibiting the lowest infectivity, number of colonies, and strength vigor index. Conversely, room temperature without packaging demonstrated the highest physiological quality in terms of seed germination and length. However, the temperature and packaging conditions are optimal for the growth of paddy seeds, i.e., at room temperature without packaging.